Fire and fury : inside the Trump White House - Wolff, Michael, 1953- (Little, Brown, 2018)
Michael Wolff tells the story of the stormy first nine months of Donald Trump's term as President. Among the revelations: What President Trump's staff really thinks of him -- What inspired Trump to claim he was wire-tapped by President Obama -- Why FBI director James Comey was really fired -- Why chief strategist Steve Bannon and Trump's son-in-law Jared Kushner couldn't be in the same room -- Who is really directing the Trump administration's strategy in the wake of Bannon's firing -- What the secret to communicating with Trump is -- What the Trump administration has in common with the movie The Producers.